2004
DOI: 10.21236/ada459397
|View full text |Cite
|
Sign up to set email alerts
|

The KOJAK Group Finder: Connecting the Dots via Integrated Knowledge-Based and Statistical Reasoning

Abstract: Link discovery is a new challenge in data mining whose primary concerns are to identify strong links and discover hidden relationships among entities and organizations based on low-level, incomplete and noisy evidence data. To address this challenge, we are developing a hybrid link discovery system called KOJAK that combines state-of-theart knowledge representation and reasoning (KR&R) technology with statistical clustering and analysis techniques from the area of data mining. In this paper we report on the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Therefore, finding important or strong connections to a seed suspect is likely to turn up other suspects ("guilt by association"), which is a phenomenon also exploited by some group detection algorithms [18]. The result reveals an interesting phenomenon where suspects have both important and abnormal connection with other suspects, since they can be detected with both types of mechanisms.…”
Section: Table 3 Performance Results For Various Algorithms On the Simentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, finding important or strong connections to a seed suspect is likely to turn up other suspects ("guilt by association"), which is a phenomenon also exploited by some group detection algorithms [18]. The result reveals an interesting phenomenon where suspects have both important and abnormal connection with other suspects, since they can be detected with both types of mechanisms.…”
Section: Table 3 Performance Results For Various Algorithms On the Simentioning
confidence: 98%
“…For semantic graphs, Adibi et al [18] describe a method combining a knowledge-based system with MI analysis to identify threat groups given a set of seeds. Krebs [5] applied SNA to the 9/11 terrorists network and suggested that to identify covert individuals; it is preferable to utilize multiple types of relational information to uncover the hidden connections in evidence.…”
Section: Network Analysis For Homeland Security and Crimementioning
confidence: 99%
“…[4] address a variant of this problem: given an edge-weighted undirected graph, two vertices s, t, and an integer k, find a connected subgraph H of size k containing s, t that maximizes a given goodness function. Other approaches have been proposed to discover groups of persons (e.g., [1]) or simplify networks (e.g., [12]). However, these approaches do not provide algebras to manipulate the objects that are produced.…”
Section: Declarative Specification Of Web Regionsmentioning
confidence: 99%
“…Recent development in link mining [22] of social networks focuses on object ranking [6,32,54], object classification [9,25,36,43,52], group detection [1,33,34,51,65,67], entity resolution [6,7,15], link prediction [13,37,38,40,53], subgraph discovery [31,35,75], graph classification [20,21], and graph generative models [20,68]. Object ranking [6,32,54] utilizes the link structure of a network to prioritize the objects which are represented as nodes in a network.…”
Section: Social Network Analysismentioning
confidence: 99%